The Learning Ecosystem of the Pancasila Student Profile Strengthening Project (P5): A Holistic Approach to Enhancing Moral Character within the Merdeka Curriculum - M. ARIF NANANG QOSIM; CHALIMATUS SA’DIYAH; MUHAMMAD FAIZ MUJIB; HANNAH (Universitas PGRI Kanjuruhan Malang, 2026)
The implementation of the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum still faces challenges, including limited teacher understanding, weak stakeholder synergy, and a learning ecosystem that has yet to optimally support students' social-moral character development. This study aims to conduct a holistic analysis of the P5 learning ecosystem and identify collaborative strategies to support the internalization of Pancasila values. The method used is a literature review examining relevant scientific literature and policy documents on P5, the Merdeka Curriculum, and character education. Findings show that the effectiveness of P5 depends on synergy among teachers as moral role models, students as agents of change, a supportive school culture, family involvement, and community collaboration. Social-moral character strengthening proves more effective when learning is linked to contextual experience and the habituation of values in daily life. Thus, P5's success requires a collaborative and sustainable educational ecosystem to shape students with character aligned with Pancasila values.